Open Space for the Third Other in Levinas: Philosophy of Dialogue as Interlocution among Filipino Tripeople and Beyond - Del Rosario, Jaime (Social Sciences and Development Review, 2023)
Philosophy of dialogue in Emmanuel Levinas’ discourses of the I, you Other, and the broader Third Other calls for opening the usual ongoing dialogue between Muslim Filipinos and Christian Filipinos into an interlocution among Tripeople, including the indigenous Filipinos. Particularly in the setting of the Bangsamoro region in Mindanao as continuing from the original Filipino people as the indigenous people who, through time, were termed as Filipino people, eventual Muslims, and Christians emerged from among those of the indigenous people who assented to such significant religions, while some remained in their indigenous beliefs. Hence, the dialogue between the I and you Other as theMuslim Filipinos and Christian Filipinos are both summoned to transcend their conversation to move towards responding to the Call of the Infinite through the Third Other than the indigenous Filipinos deserve such open space for the broader interlocution among them as Filipino Tripeople. The Call of the Infinite Goodness, however, proceeds even beyond the three of these communities among Filipinos. The hybridities emerging among them extend into their international relations as the Infinite moves even further to the Good of the human race that each of them is summoned to fulfill. The Good of the other and the third other calls for transcending the self of the I. Inherent in the original I of the Filipino person has been expressed in belonging to open communities that extend to different others, such that the kababayan in a village or barangay is not confined to kinship but to the inherent Filipino view of shared humanity. Filipino proverbs, including those of diverse ethnic groups, open the identity of the humanity of the Filipino to religiously different others. Thus, conflicts of differences would be resolved peacefully by interreligious openness to the inherent friendship to the point of siblinghood in their human interactions. Inherent traits among Filipinos then are the elements that open space for transforming violence towards a shared community that they used to blend, valuing the life of the others and shared charitable care for the others to fulfill the I of the Filipino. Respect for the natural environment as the inherent habitat of the indigenous Filipinos can move the Tripeople towards a shared vision that responds to an even further infinite call for Goodness of international relations with the entire human race
Keywords: Philosophy of Dialogue as Interlocution; Filipino Tripeople as Muslims; Christians, and Indigenous People; Interreligious dialogue; Transcendence; Third Other in Levinas